Safety, Pharmacokinetics, Pharmacodynamics, and Antitumor Activity of Necuparanib Combined with Nab‐Paclitaxel and Gemcitabine in Patients with Metastatic Pancreatic Cancer: Phase I Results. (4th December 2017) - O'Reilly, Eileen M.; Roach, James; Miller, Paul; Yu, Kenneth H.; Tjan, Catherine; Rosano, Molly; Krause, Silva; Avery, William; Wolf, Julie; Flaherty, Keith; Nix, Darrell; Ryan, David P.
Abstract: Lessons Learned : Despite the compelling preclinical rationale of evaluating the genetically engineered heparin derivative, necuparanib, combined with standard therapy in metastatic pancreas adenocarcinoma, the results were ultimately disappointing. Safety was documented, although dose escalation was limited by the number of subcutaneous injections, the potential for skin toxicity (cellulitis), and low‐level anticoagulant effect. Nonetheless, the hypothesis of targeting prothrombotic pathways in pancreas adenocarcinoma remains compelling. Background: Necuparanib is derived from unfractionated heparin and engineered for reduced anticoagulant activity while preserving known heparin‐associated antitumor properties. This trial assessed the safety, pharmacokinetics (PK), pharmacodynamics, and initial efficacy of necuparanib combined with gemcitabine ± nab‐paclitaxel in patients with metastatic pancreatic cancer. Methods: Patients received escalating daily subcutaneous doses of necuparanib plus 1, 000 mg/m 2 gemcitabine (days 1, 8, 15, and every 28 days). The protocol was amended to include 125 mg/m 2 nab‐paclitaxel after two cohorts (following release of the phase III MPACT data). The necuparanib starting dose was 0.5 mg/kg, with escalation via a modified 3 + 3 design until the maximum tolerated dose (MTD) was determined. Results: Thirty‐nine patients were enrolled into seven cohorts (necuparanib 0.5, 1 mg/kg + gemcitabine; necuparanib 1, 2, 4, 6, and 5 mg/kg + nab‐paclitaxel + gemcitabine). The most common adverse events were anemia (56%), fatigue (51%), neutropenia (51%), leukopenia (41%), and thrombocytopenia (41%). No deaths and two serious adverse events were potentially related to necuparanib. Measurable levels of necuparanib were seen starting at the 2 mg/kg dose. Of 24 patients who received at least one dose of necuparanib + nab‐paclitaxel + gemcitabine, 9 (38%) achieved a partial response and 6 (25%) achieved stable disease (63% disease control rate). Given a cellulitis event and mild activated partial thromboplastin time increases at 6 mg/kg, the 5 mg/kg dose was considered the MTD and selected for further assessment in phase II. Conclusion: Acceptable safety and encouraging signals of activity in patients with metastatic pancreatic cancer receiving necuparanib, nab‐paclitaxel, and gemcitabine were demonstrated.